Redox partner exchanges between spatially confined complexes control the coupling effect of cytochrome b5 on P450 CYP3A4 - Philippe Urban; Alain Perret; Denis Pompon (Scientific Reports)
Abstract Cytochrome b5 (b5) plays an important role in the enhancement of the activity of specific cytochrome P450s, especially CYP3A4. Contradictory interpretations were proposed that alternatively defend conformational or redox-based mechanisms. A semi-synthetic system involving CYP3A4, its reductase (CPR), and native or modified b5 bound to the ER membrane was used to clarify this question. This took advantage of the use of b5 analogs featuring cofactors with modified redox properties, in combination with rapid kinetic experiments, activity determinations, and structural predictions. The results supported a redox-based mechanism of activation in which the b5 molecules remain partially confined with specific CYP3A4 partners throughout the catalytic cycle, acting both as an electron acceptor and donor. Structural models of corresponding complexes were built using AlphaFold predictions supplemented by holoenzyme reconstruction and molecular dynamics. Results supported the formation of mutually exclusive CPR-P450 and b5-P450 binary complexes, each with electron transfer capacity. The potential formation of an unusual ternary complex allowing a more delocalized electron exchange between P450 heme, FAD, FMN of CPR and b5 heme was also considered. Modeled formation of these alternate complexes also provided potential structural interpretations for non-redox complementary mechanisms that could contribute to the global activation mechanism of CYP3A4.